Internet censorship detected in Iran (Iran) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Iran. Data sourced from CensoredPlanet.
Censorship Incident ID: IR-2026-0385. Severity: critical. Confidence: 65%